Board structure, mergers, and shareholder wealth: a study of the mutual fund industry - Tufano, P; Khorana, A; Wedge, L (2004)
We study mutual fund mergers between 1999 and 2001 to understand the role and effectiveness of fund boards. Some fund mergers—typically across-family mergers—benefit target shareholders but are costly to target fund directors. Such mergers are more likely when funds underperform and their boards have a larger percentage of independent trustees, suggesting that more-independent boards tolerate less underperformance before initiating across-family mergers. This effect is most pronounced when all of the fund's directors are independent, not the 75% level of independence required by the SEC. Higher-paid target fund boards are less likely to approve across-family mergers that cause substantial reductions in their compensation.